Кисломолочні напої з наповнювачем з пророщеного жита - Усатюк, Світлана Іванівна; Королюк, Тамара Андріївна; Вознюк, А. В.; Демчина, Галина Любомирівна; Цабілева, Людмила Вікторівна (My University, 2012)
У статті наведено основні технологічні етапи отримання кисломолочного напою з додаванням пророщеного жита. Встановлено оптимальні умови для пророщування жита та співвідношення молока і жита в рецептурі напою. Підібрано форму наповнювача для внесення до напою. Обрано бактеріальний препарат для сквашування молока. Отриманий кисломолочний напій збагачений поживними речовинами завдяки додаванню пророщеного жита. The investigations carried out about producing sour milk product with addition of germinated rye. Chosen mode of rye germination helps increase protein contain in the product and amilolitic activity enzyme. By the investigations the optimal proportion of milk and germinated rye in the product was found (80:20). Usage of natural addition from germinated rye meliorates organoleptic properties of the product and helps provide necessary quality of the bfwerage. The minimal souring time (5 hours) was found whil з souring milk by bacterial preparation including Streptococcus salivarius ssp, Thermoph lus, Lactobacillus bulgaricus and Lactobacillus acidophilus cultures. Souring was carried с ut at the temperature 37 °С, during 5 hours. Optimal quantity of the bacterial preparation (3 % of the product mass) was determined by the experimental way. Such quantity of the bacterial preparation provides necessary active acidity of the product. The beverage has biological value and pleasant taste. Consuming of the product helps compensate for the lack of vitamins in nutrition of реорЬз and stimulate metabolism. The technology may be recommended to be inculcated in milk produce industry.
Keywords: бактеріальні препарати; bacterial drugs; молоко; сквашування; кисломолочний напій; пророщене жито; milk; souring; sour milk product; germinated rye; кафедра експертизи харчових продуктів